1998
DOI: 10.1021/cm980185x
|View full text |Cite
|
Sign up to set email alerts
|

New Hydrotalcite-like Anionic Clays Containing Zr4+in the Layers:  Synthesis and Physicochemical Properties

Abstract: A new series of hydrotalcite (HT)-like anionic clays containing Zr 4+ in the brucite-like layer has been synthesized by a simple coprecipitation method at constant pH. The incorporation of Zr in the layer has been investigated by various analytical methods, such as powder X-ray diffraction (PXRD), chemical analysis, FT-IR, ultraviolet-visible diffuse reflectance (UV-vis DR) spectra, and thermogravimetric analysis (TGA). The PXRD of assynthesized samples showed that the crystallinity of the material decreased w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 30 publications
(59 reference statements)
2
41
1
4
Order By: Relevance
“…The incorporation of tetravalent cations such as zirconium ions into the LDH layers have been also reported by Velu et al [38,39], Tichit et al [22], and Das et al [40]. Otherwise, Intissar et al analyzed the ill-crystalline Zr-MgAl-LDH prepared by the coprecipitation method according to Velu et al [38,39] using XAS spectroscopy [41]. They concluded that the incorporation of zirconium ions into LDH layers did not occur in the case of the ill-crystalline Zr-MgAl-LDH, and suggested that amorphous ZrO 2 -like oxides might be formed.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…The incorporation of tetravalent cations such as zirconium ions into the LDH layers have been also reported by Velu et al [38,39], Tichit et al [22], and Das et al [40]. Otherwise, Intissar et al analyzed the ill-crystalline Zr-MgAl-LDH prepared by the coprecipitation method according to Velu et al [38,39] using XAS spectroscopy [41]. They concluded that the incorporation of zirconium ions into LDH layers did not occur in the case of the ill-crystalline Zr-MgAl-LDH, and suggested that amorphous ZrO 2 -like oxides might be formed.…”
Section: Introductionsupporting
confidence: 55%
“…The superior phosphate adsorption property of the novel Zr-MgAl-LDH was explained by the incorporation of the zirconium ions into the LDH layers. The incorporation of tetravalent cations such as zirconium ions into the LDH layers have been also reported by Velu et al [38,39], Tichit et al [22], and Das et al [40]. Otherwise, Intissar et al analyzed the ill-crystalline Zr-MgAl-LDH prepared by the coprecipitation method according to Velu et al [38,39] using XAS spectroscopy [41].…”
Section: Introductionmentioning
confidence: 89%
“…To investigate the incorporation of tetravalent cations into the LDH structure is interesting task because there is no clarity concerning incorporation of tetravalent metals in LDHs. Some of studies reported the possibility of synthesizing LDHs containing M(IV) ions [5,[19][20][21][22][23][24]. Another authors based on results of X-ray absorption spectroscopy (XAS) and Mössbauer spectroscopy [25] concluded that the M(IV) cations are segregated from LDH structure and may form amorphous M(IV) oxide-like particles.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported by several authors [28,34,35] that in the case of Mg/Al LDHs, thermal decomposition at 400-500 8C yields an ill-crystallized MgO phase whose lattice constant a is less than that of pure MgO and has been attributed to the dissolution of a small amount of Al 3+ in the MgO lattice to form solid solutions. This lattice parameter a of the resulting MgO-like cubic phase (MgO solid solution) was evaluated from both d(2 0 0) and d(2 2 0) peaks, using the relation a = d  (h 2 + k 2 + l 2 ) 1/2 and the values for the catalysts are shown in Table 1.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%